2021
DOI: 10.3390/vaccines9050420
|View full text |Cite
|
Sign up to set email alerts
|

Pneumonia and Invasive Pneumococcal Diseases: The Role of Pneumococcal Conjugate Vaccine in the Era of Multi-Drug Resistance

Abstract: Streptococcus pneumoniae related diseases are a leading cause of morbidity and mortality, especially in children and in the elderly population. It is transmitted to other individuals through droplets and it can spread to other parts of the human host, causing a wide spectrum of clinical syndromes, affecting between 10 and 100 cases per 100,000 people in Europe and the USA. In order to reduce morbidity and mortality caused by this agent, pneumococcal vaccines have been developed over the years and have shown in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 123 publications
(197 reference statements)
1
25
0
Order By: Relevance
“…[1] PCV use has also substantially reduced hospital visits from pneumococcal otitis media and antibiotic use and has the potential to reduce antimicrobial resistance. [2][3][4] Nonetheless, Streptococcus pneumoniae (the pneumococcus) remains a leading cause of pneumonia and invasive diseases (meningitis, bacteraemic pneumonia and bacteraemia). [1] In 2015, pneumococcal disease still caused approximately 300,000 deaths among children aged 1-59 months globally, and over 50% of these deaths occurred in the African sub-region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] PCV use has also substantially reduced hospital visits from pneumococcal otitis media and antibiotic use and has the potential to reduce antimicrobial resistance. [2][3][4] Nonetheless, Streptococcus pneumoniae (the pneumococcus) remains a leading cause of pneumonia and invasive diseases (meningitis, bacteraemic pneumonia and bacteraemia). [1] In 2015, pneumococcal disease still caused approximately 300,000 deaths among children aged 1-59 months globally, and over 50% of these deaths occurred in the African sub-region.…”
Section: Introductionmentioning
confidence: 99%
“…adjusted for symptoms of upper respiratory tract infection in past two weeks, living with≥2 under-fives, and age-standardised to age distribution of study sites; 2 prevalence ratios across all surveys from date of PCV10 introduction to date of swabbing coded as a single time variable to obtain estimate of prevalence ratio per year; 3 Five surveys (2016-2020);4 Four surveys (2017-2020); 5 prevalence ratio comparing final survey in each site to the 1 st survey.…”
mentioning
confidence: 99%
“…Infections caused by Streptococcus pneumoniae are prevalent worldwide, with particularly high morbidity and mortality in children and the elderly [1]. In 2005, the World Health Organization estimated that 1.6 million deaths per year were caused by S. pneumoniae [1].…”
mentioning
confidence: 99%
“…Infections caused by Streptococcus pneumoniae are prevalent worldwide, with particularly high morbidity and mortality in children and the elderly [1]. In 2005, the World Health Organization estimated that 1.6 million deaths per year were caused by S. pneumoniae [1]. S. pneumoniae is a commensal bacterium that settles in the human nasopharynx, causing not only noninvasive diseases such as otitis media, sinusitis, and pneumonia, but also invasive and life-threatening diseases such as bacteremia, sepsis, and meningitis.…”
mentioning
confidence: 99%
“…Studies have revealed that childhood immunisation has led to reduced adult pneumococcal disease through herd effects [ 5 ]. However, this is less marked in populations with risk factors [ 6 ], and disease burden based on IPD surveillance is often underestimated.…”
Section: Introductionmentioning
confidence: 99%